Wanprestasi (Kredit Macet) Dalam Perjanjian Leasing Berdasarkan Putusan Peraturan Menteri Keuangan No. 130/pmk.010/2012 dan Putusan Mahkamah Konstitusi No. 18/ppu-xvii/2019 - Fajar Fajar (Universitas Muara Bungo, 2021)
AbstractLeasing companies in Indonesia are currently very mushrooming because the financing processes and procedures tend to be easy and fast. The leasing company is present to provide financing, preceded by a leasing agreement, then the agreement creates rights and obligations between the financier (lessor) and the financing recipient (lesse). Leasing companies are subject to law Number 42 of 1999 concerning fiduciary guarantees, leasing companies are required to register objects of fiduciary guarantees at the fiduciary registration office in order to obtain legal certainty so that in the event of default (bad credit) the lessor will not be harmed in the future. In terms of the execution of the object of fiduciary security after the issuance of the Constitutional Court Decision No. 18/ XVII PPU- /2019, the authority to execute the object of fiduciary security is no longer with the leasing company but based on the decision of the district court. This is to provide legal protection to the lesse so that the lessor's arbitrariness does not occur in an effort to force the execution of a fiduciary object. Keywords: Lack of Agreement, Leasing Agreement, Fiduciary Security AbstrakPerusahaan leasing di Indonesia saat ini sangat menjamur karena proses dan prosedur pembiayaan cenderung mudah dan cepat prosesnya. Perusahaan leasing hadir memberikan pembiayaan dengan didahului oleh perjanjian leasing kemudian perjanjian tersebut menimbulkan hak dan kewajiban antara pihak pemberi pembiayaan (lessor) dan pihak penerima pembiayaan (lesse). Perusahaan leasing tunduk pada Undang-Undang Nomor 42 Tahun 1999 tentang Jaminan Fidusia, perusahaan leasing wajib mendaftarkan objek jaminan fidusia pada kantor pendaftaran fidusia guna mendapatkan kepastian hukum agar ketika teradi wanprestasi (kredit macet) di kemudian hari pihak lessor tidak dirugikan. Dalam hal eksekusi objek jaminan fidusia setelah dikeluarkannya Putusan Mahkamah Konstitusi No. 18/PPU-XVII/2019 maka kewenangan mengeksekusi objek jaminan fidusia tidak lagi pada perusahaan leasing melainkan berdasarkan putusan pengadilan negeri. Hal ini guna memberikan perlindungan hukum kepada lesse agar tidak terjad kesewenang-wenangan pihak lessor dalam upaya paksa melakukan eksekusi objek fidusia. Kata Kunci: Wanprestasi, Perjanjian Leasing, Jaminan Fidusia